Karen Mohr-Chávez (1941-2001) - Chirinos, Patricia (Pontificia Universidad Católica del Perú. Fondo Editorial, 2001)
Karen L. Mohr-Chavez (1941-2001)The text doesn't have an abstract
Keywords: Arqueología; Karen Mohr-Chávez; Arqueología de la Sierra Sur; Chiripa; Pucara; Tradición Yaya-Mama; Archaeology; Karen Mohr-Chávez; South Highland Archaeology; Chiripa; Pucara; Yaya-Mama Tradition; https://purl.org/pe-repo/ocde/ford#6.01.02